(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
Initial-boundary value problems for equations of a hyperbolic type are widely used in mathematical physics, technical science and other fields. For instance, describing a large class of natural phenomena: solving of wave equations, concepts of the classical and generalized suolution, as well as their difference and existence is given the target thesis For the different types of equations constructing of boundary conditions and their types, Cauchy problems with initial-boundary value problems are covered for the mixed issues. Classical mathematical physics problems are presented brought solving boundary value problems for second-order particular derivative differential equations. In the circumstance, finding and learning the initial-boundary value problems for the higherorder particular derivative mixed equations have become an urgent problem. Existence of the solutions of particular derivative mixed problems constructing with initialboundary value conditions and researched finding of them. When none of the classical solution in the given problem, might be find generalized solution with the generalized functions corresponding to that. funksiyalar bilan umumlashgan yechimni topish mumkin.